2020
DOI: 10.21203/rs.3.rs-31855/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of SARS-CoV2-mediated suppression of NRF2 signaling reveals a potent antiviral and anti-inflammatory activity of 4-octyl-itaconate and dimethyl fumarate

Abstract: Antiviral strategies to inhibit Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2) and the pathogenic consequences of COVID-19 are urgently required. Here we demonstrate that the NRF2 anti-oxidant gene expression pathway is suppressed in biopsies obtained from COVID-19 patients. Further, we uncover that NRF2 agonists 4-octyl-itaconate (4-OI) and the clinically approved dimethyl fumarate (DMF) induce a potent cellular anti-viral program, which potently inhibits replication of SARS-CoV2 across cell line… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…The viral replication, in turn, triggers the activation of monocytes, macrophages, granulocytes resulting in the hyper inflammatory condition described as "cytokine storm" with the massive secretion of pro-inflammatory cytokines including interleukin (IL)-1, IL-6, IL-8, IL-12, tumor necrosis factor (TNF)-α, etc. This results in hyper inflammation of tissues and subsequent tissue fibrosis and pneumonia (4,7,10). Studies also indicate the involvement of oxidative stress in the pathogenesis of COVID-19.…”
Section: Pathogenesis Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…The viral replication, in turn, triggers the activation of monocytes, macrophages, granulocytes resulting in the hyper inflammatory condition described as "cytokine storm" with the massive secretion of pro-inflammatory cytokines including interleukin (IL)-1, IL-6, IL-8, IL-12, tumor necrosis factor (TNF)-α, etc. This results in hyper inflammation of tissues and subsequent tissue fibrosis and pneumonia (4,7,10). Studies also indicate the involvement of oxidative stress in the pathogenesis of COVID-19.…”
Section: Pathogenesis Of Covid-19mentioning
confidence: 99%
“…In another study done on human HCoV-229E infection shows that deficiency in the expression of NRF-2 target, glucose-6-phosphate dehydrogenase (G6PDH) results in enhanced ROS as well as virus production (14). Incidentally, the NRF-2 levels were found to be suppressed in lung biopsies from COVID-19 subjects, on the other hand NRF-2 activators found to inhibit replication of SARS-CoV-2 and the inflammatory response (10). However, it is not known how SARS-CoV-2 infection causes suppression of NRF-2 signaling.…”
Section: Pathogenesis Of Covid-19mentioning
confidence: 99%
“…Given that changes in redox homeostasis in infected cells and lung inflammation are hallmarks of infections caused by respiratory viruses [ 70 ], the information obtained from viruses that affect the airways may be relevant for extrapolation to COVID-19. Indeed, experimental evidence is beginning to emerge, and it was recently demonstrated that the NRF2 activators dimethyl fumarate (DMF) and 4-octyl itaconate (4-OI), a cell-permeable analog of the endogenous anti-inflammatory metabolite itaconate [ 22 ], suppress the inflammatory response to SARS-CoV2 in human cells, including peripheral blood mononuclear cells (PBMCs) from COVID-19 patients [ 33 ].…”
Section: Armamentarium Of Available Nrf2 Activators For Potential Antmentioning
confidence: 99%
“…X-206 (12 nM) was effective at all time points with the most significant reduction in viral mRNA (measured 24 h after infection) observed at either 0.5 h pre-infection or 2h post-infection ( Figure 3 C). We also measured the TCID50/mL ( Olagnier et al, 2020 ) which demonstrated a nearly 2-fold log-reduction of infectious viral progeny in the supernatent at all time points ( Figure 3 D).
Figure 3 Comparison of polyether ionophores with cationic amphiphiles and time-dependence of the anti-viral activity of X-206.
…”
mentioning
confidence: 99%